A critical legal conception of human dignity. Issue 1 (1st January 2019) - McManus, Matthew
Abstract: In this article, I argue for adopting a specific conception of human dignity centered around the argument that human dignity flows from an individual's capacity for self-authorship as defined by the set of expressive capabilities they enjoy. I also develop a corollary argument for a specific model of fundamental rights which flows from adopting the conception of dignity presented here.